PENGARUH LAMA MENGAJAR MENGGUNAKAN MEDIA LAPTOP TERHADAP TERJADINYA MYOFACIAL PAIN SINDROME REGIO UPPER BACK MUSCLES PADA DOSEN IKEST MUHAMMADIYAH PALEMBANG - juliastuti juliastuti juliastuti; Imam Haryoko (IKesT Muhammadiyah Palembang, 2022)
Background: Myofascial pain syndrome (MTPS) is a condition with many collections of signs and symptoms caused by damage to the structure of fascia and muscle tissue. Some of the signs and symptoms include trigger points in the hyperirritated muscle region and hypersensitivity to the link bands in muscles with myofascial pain syndrome, which will feel painful when pressed, and there are specific characteristics, namely Referred Pain, Motor Dysfunction, and Autonomic Phenomena. . Purpose : This study aims to determine the effect of teaching time using laptop media on Myofascial pain syndrome Upper back muscles at IKesT Muhammadiyah Palembang lecturers. Methods: The research was conducted observationally using the Cross Sectional (Chi Square) analytic method with a Point Time Approach design. Results: The results of the study obtained p value = 0.004 it can be concluded that the difference in the proportion of the incidence of teaching time using a laptop on the occurrence of MTPS complaints. The conclusion of this research is that there is a relationship between the length of time teaching using a laptop to the occurrence of Myofascial Pain Syndrome. Recommendations for this research can be continued with research with treatment of respondents Keywords: Long Teaching Time, Myofascial Pain Syndrome